Primary sedimentation tank model with characterized settling velocity groups - Polorigni, Christian Leprince (University of Cape Town, 2021)
Primary sedimentation involves the separation of solids and liquid in primary settling tanks (PSTs) of wastewater treatment systems. These physical processes are described by various settling conditions such as discrete and flocculent settling, along with other phenomena such as flocculation, coagulation, ammonification or hydrolysis. The modelling of primary sedimentation has often been overlooked because (i) it involves various intricacies that are difficult to replicate and (ii) primary sedimentation has been assumed to be an input to most of the main unit process models, including the activated sludge (AS) system and the anaerobic digestion (AD) models. Though there has been a wide range of proposed mathematical models to describe how PSTs function, the need to correctly disaggregate the total suspended solids (TSS) into realistic fractions of unbiodegradable particulate organics (UPO), biodegradable particulate organics (BPO) and inorganic settleable solids (ISS), remains. This is because PST models that are unable to correctly split the TSS into its characteristic components make incorrect assumptions. These assumptions lead to inconsistencies in predicting the compositions of the primary sludge (PS) that is fed to the AD unit and the settled wastewater (settled WW) that is treated in the AS system. Hence, it becomes difficult to correctly simulate the entire system (plant-wide) towards a holistic evaluation of system strategies. In this study, a realistic PST model was developed, with characterized settling velocity groups, within a plant-wide setting, for municipal wastewater. This involved the improvement of a current TSS-based model into a more accurate and realistic model that could account for the settling of raw wastewater particles. The model was therefore expected to predict the composition of the PS that is treated in the AD system and the composition of the settled WW that is going to the AS unit processes. This could be achieved by splitting the TSS into UPO, BPO and ISS fractions. In developing preparation of such a realistic PST model, the following objectives were established: 1. Disaggregate the TSS into realistic UPO, BPO and ISS fractions, by means of discrete particle settling modelling (Kowlesser, 2014) and the particle settling velocity distribution (PSVD) approach of Bachis et al. (2015). 2. Verify that the model is internally consistent with wastewater treatment plant (WWTP) data, by means of mathematical material mass balances and other specific scenarios. 3. Demonstrate the application and impact of such a model by performing steady state plant-wide simulations. Using the discrete particle settling approach of Kowlesser (2014), a discrete particle settling model was developed in Microsoft Excel and implemented into a dynamic PST framework in WEST® (Vanhooren et al., 2003). The discrete particle settling model was described using steady state and dynamic calculations and the insights obtained from these calculations were implemented in the current TSS-based PST model of Bachis et al. (2015). This was performed towards developing the University of Cape Town Primary Sedimentation Unit (UCTPSU). The influent raw wastewater TSS was fractionated into UPO, BPO and ISS fractions and settling proportions of these fractions were assigned to five settling velocity groups. In addition, a distinct settling velocity was assigned to each settling velocity group. Previous studies data from WRC (1984) and Ekama (2017), were used in the discrete particle settling model, which was able to reproduce PS and settled WW outputs, through steady state and dynamic calculations and under strict material mass balances. As a result, UPO, BPO and ISS settling proportions as well as settling velocities, were extracted from these calculations and used as input parameters into the UCTPSU model. This dynamic model was rigorously verified to be internally consistent with regards to strict material mass balances. The verification scenarios also included variations of high and low settling velocities as well as a combination of both high and low velocities and checking that the model was behaving as expected. The application and impact of the UCTPSU model were demonstrated using plant-wide scenarios in proposing a preliminary integration, under steady state conditions. It showed how incorrect disaggregation of the TSS into UPO, BPO and ISS fractions can lead to incorrect predictions in terms of the settled WW composition, the AS system capacity, the effluent quality, as well as the energy consumption and generation in the AS system and AD unit respectively. The investigation also revealed the need to measure key wastewater parameters such as particle settling velocities and the unbiodegradable particulate COD fraction, when it comes to realistically modelling of primary sedimentation of municipal wastewater, with the view of optimizing plant operations and tactical decision making. The study thereafter recommended the need to conduct an extensive experimental campaign to measure in-situ diurnal data, mainly in terms of settling velocities and settling proportions of UPO, BPO and ISS. It was also suggested to use the settleometer as a tool to extract these settling velocities and settling proportions, after performing biodegradability tests. As such, the data collected from the experimental campaign and the biodegradability tests could be used in calibrating the UCTPSU model and validation could be undertaken by means of full plant scale data.